2008 38th Annual Frontiers in Education Conference 2008
DOI: 10.1109/fie.2008.4720641
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Peer Led Team Learning in first-year programming courses

Abstract: In the Peer Led Team Learning model (PLTL) many of the skills developed by students correlate well with desired learning outcomes in CSET programs. The authors report the results of a project to implement PLTL in introductory programming courses.An overview of the implementation model is provided, lessons learned are reported, and the assessment process and results are described. The research questions explored are: (1) What is the impact of the PLTL model on student skills and confidence regarding teamwork, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…PLTL student success measures were evaluated in a variety of undergraduate disciplines, including: general chemistry; ,,− organic chemistry; allied health, which is also called GOB; introductory biology; , anatomy and physiology; bioinformatics; mathematics; computer science; , engineering; psychology; and physics . Although implementation of PLTL has been reported in a high school setting, no peer-reviewed articles were available at the time of this review article.…”
Section: Student Success Measures As a Means Of Program Evaluationmentioning
confidence: 99%
“…PLTL student success measures were evaluated in a variety of undergraduate disciplines, including: general chemistry; ,,− organic chemistry; allied health, which is also called GOB; introductory biology; , anatomy and physiology; bioinformatics; mathematics; computer science; , engineering; psychology; and physics . Although implementation of PLTL has been reported in a high school setting, no peer-reviewed articles were available at the time of this review article.…”
Section: Student Success Measures As a Means Of Program Evaluationmentioning
confidence: 99%
“…The workshops center on discussions and problem-solving, and provide a stress-free environment for dealing with course-related challenges. This approach has also been successfully adopted for introductory computer science education [Utschig and Sweat 2008]. Peer-led team learning is a form of learning that can be controlled for time and can encourage communication, though may be challenging to implement online.…”
Section: Workload Expectations and Timementioning
confidence: 98%
“…Whereas other authors have discussed the theoretical and observed merits of such a program [2,6,8], or focused on how to get a program off the ground [4], our intent is to share the general lessons learned so that others who are starting, growing, or modifying a PLTL program can learn from our experiences.…”
Section: Introductionmentioning
confidence: 99%